Unique protonconduction 3D ZnII metal organic framework exposure to aquaammonia vapor to enhance conductivity. (7th April 2022) - Liu, Ruilan; Li, Jie; Zhu, Wenping; Yang, Weijie; Li, Yanxia; Liu, Zengchen; Chen, Yahong; Li, Gang
Abstract : The Zn II MOF with proton-conductivity obtained an optimal conductivity of 1.38 × 10 −3 S cm −1 (100 °C) under 2 M aquaammonia vapor. Abstract : Recently, metal–organic frameworks (MOFs) have been receiving increasing attention because their modular building blocks give them diversity and functional adjustability. MOFs have achieved excellent results as novel proton-conducting materials. However, there are relatively limited studies on the properties of proton-conducting MOFs that can be regulated by changing the test environment. Herein we explored the proton conductivity of a Zn II MOF [Zn3 ( m -MOD)2 (H2 O)6 ]·4H2 O n (ZS-1 ) ( m -MOD = 2-(3-methoxy phenyl)-1 H -imidazole-4, 5-dicarboxylicacid) at humidity and aquaammonia vapor. ZS-1 has a 3D structure in the shape of a windmill, which contains hexagonal one-dimensional channels and a large number of free and coordination water molecules, providing convenient conditions for proton conduction. ZS-1 obtained an optimal conductivity of 1.38 × 10 −3 S cm −1 (100 °C) under 2 M aquaammonia vapor, which was about three orders of magnitude higher than the maximum conductivity under water vapor (5.31 × 10 −6 S cm −1, 100 °C-98% RH). The proton conduction mechanism is discussed in depth by combining the structural characteristics and related characterizations.